(3GdeNJUQ aj eUWdM Cgd GdCKQs - (3YHO Gddg Hf HgGA GdOjf GdTfThQjs ((3MSjf Hf YHOGdcQje s)
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ YHOGddg Hf GdTjN HgGA GdOjf GdTfThQj gPg ebOeI aj eUWdM Yde GdMOjK s
(3BNQgG (B:s
(3eSJZfjI Yf GdJeKjd XGgQI GdJYQja adJQGLY aj GdeHShWGJ hGddg GYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B- (3GdehUd (B(55) s
Keywords: (3GdMOjK h GdeUWdMs